EFFECT OF GOOD CORPORATE GOVERNANCE AND WHISTLEBLOWING SYSTEM ON FRAUD IN GENERAL ELECTRICITY COMPANY OF LIBYA - Alsdai, Abobakr Ali (Jurnal Kewirausahaan dan Inovasi, 2023)
The purpose of this study was to determine the effect of Good Corporate Governance and Whistle Blowing System on Fraud. The population in this study were employees of General Electricity Company Libya. The analysis technique used multiple regression analysis techniques. The data analysis method used is a statistical analysis method using IBM SPSS Statistics 25 software. The results showed that Good Corporate Governance affects Fraud and Whistle Blowing System has an effect on Fraud. Based on the conclusions above, the researcher provides advice to companies to carry out monitoring which can be carried out either suddenly or on a scheduled basis to find out how far the implementation of good corporate governance has been carried out in the company for the purpose of preventing fraud. This is intended so that if there are deficiencies or errors in the existence of good corporate governance, they can be corrected immediately and not interfere. Company leaders should also evaluate the policy of implementing the violation reporting system that has been implemented so that it can be seen to what extent the response from employees is if there is any intention or desire to participate in reporting fraud that occurred in its division and the surrounding environment.